Advertisement Remove all ads

Solve the following pair of linear equations ax + by = c, bx + ay = 1 + c - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads

Solve the following pair of linear equations

ax + by = c

bx + ay = 1 + c

Advertisement Remove all ads

Solution

ax + by = c … (1)

bx + ay = 1 + c … (2)

Multiplying equation (1) by a and equation (2) by b, we obtain

a2aby ac … (3)

b2x + aby = b + bc … (4)

Subtracting equation (4) from equation (3),

(a2 − b2ac − bc − b

 

`x = (c(a-b)-b)/(a^2 - b^2)`

From equation (1), we obtain

ax + by = c

`a{((c(a-b)-b))/(a^2-b^2)}+by = c`

`(ac(a-b)-ab)/(a^2-b^2)+by=c`

`by = c - (ac(a-b)-ab)/(a^2-b^2)`

`by = (a^2c-b^2c-a^2c+abc+ab)/(a^2-b^2)`

`by= (abc-b^2c+ab)/(a^2-b^2)`

`by = (bc(a-b)+ab)/(a^2-b^2)`

`y= (c(a-b)+a)/(a^2-b^2)`

Concept: Equations Reducible to a Pair of Linear Equations in Two Variables
  Is there an error in this question or solution?

APPEARS IN

NCERT Class 10 Maths
Chapter 3 Pair of Linear Equations in Two Variables
Exercise 3.7 | Q 7.2 | Page 68
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×